Applying value management when it seems that there is no value to be managed: the case of nuclear decommissioning. Issue 5 (July 2019) - Invernizzi, Diletta Colette; Locatelli, Giorgio; Grönqvist, Marcus; Brookes, Naomi J.
Abstract: The vast majority of project management literature relating to infrastructure focuses on the project lifecycle up to commissioning and handover. Conversely, little attention has been paid to the end-of-life of infrastructure, i.e. when decommissioning begins. Infrastructure decommissioning projects are long and complex projects, involving an extensive network of stakeholders. Moreover, their budgets can reach hundreds of billions of Euros and, for many of these projects, keep increasing. Since decommissioning projects do not generate direct revenues, they are often considered an expensive nuisance with limited value linked to their delivery. This paper explores the use of Value Management (VM), examining the constraints of decommissioning projects and the requirements for successful implementation of VM, focusing on the nuclear industry due to its techno-socio-economic relevance. Findings derived from the application of content analysis on semi-structured interviews with experienced decommissioning practitioners include suggestions on how to implement VM, ultimately contributing to increase the knowledge on how to deliver decommissioning projects with better performance. Highlights: Project management literature has paid limited attention to decommissioning. Decommissioning projects present an array of new project management challenges. This paper examines the requirements for successful VM in nuclear decommissioning. A multidisciplinary VM team play a key role in nuclear decommissioning. An experienced VM leader and an open project delivery environment with no 'pre-conceived' options are key to success.